Fostering Supply Chain Integration through Blockchain Technology: A Study of Malaysian Manufacturing Sector - Mubarik, Mobashar; Rasi, Raja Zuraidah binti Raja Mohd; Mubarak, Muhamamad Faraz (International Journal of Management and Sustainability, 2020)
The study aims to identify the role of the blockchain-based supply chain in supply chain integration. The study also aims to investigate the role of various factors that possibly mediate the relationship between blockchain-based supply chain management and supply chain integration. The study adopted a twofold mixed-method approach—sequential explanatory— to attain the objectives. In the first phase, data were collected from Malaysian electrical and electronic firms, and by applying PLS-SEM, hypothesized relationships were examined. In the second phase, through a qualitative study, the results of the first phase are discussed with the industry experts to seek their expert opinion. In doing so, the semi-structured interview from seven experts, selected through purposive sampling, were conducted. The findings of both inquiries reveal that blockchain technology has significant potential to enhance the integration between numerous actors in multi-level supply chains while ensuring the transparency and traceability in the transactions. Moreover, the findings reveal that certain pre-requisites are missing at the moment in the Malaysian manufacturing sector, which are inevitable to be met, before implementing the block-chain based supply chain. Sophisticated infrastructure which could suffice the blockchain-based technologies implementation in supply chains and the absorptive capacity is prominent amongst them. Consequently, it is recommended that appropriate training should be given to employees in order to cater to the requirement of the technical skills needed to handle such advanced technology. Further, continuous infrastructural investments should be made to implement blockchain-based technology in the business ecosystem of Malaysia at the government level.